Investigating the Quorum Sensing System in Halophilic Bacteria - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2015)
Halophiles are organisms that inhabit hypersaline environments and require hypersaline conditions to grow (from 2-5 % NaCl up to above 20-30 % NaCl). Halophiles are mostly prokaryotes, which are able to thrive in such harsh conditions because of their capability to balance the osmotic pressure of the environment through different mechanisms. Bacteria mainly produce high concentrations of compatible solutes, small water-soluble organic molecules, which do not interfere with cell metabolism (amino acids and their derivatives, sugar and polyols). Archaea and some halophilic anaerobic bacteria accumulate high concentration of salts intracellularly (KCl). Halophilic bacteria produce biomolecules with great potential for biotechnology: exopolysaccharides, compatible solutes (which can be used as stabilizers of biomolecules) and stable enzymes (with potential use as biocatalysts). Quorum sensing (QS) could influence the production of these biomolecules, thus a better understanding of halophilic bacterial communication mechanisms can help to improve the yields of these biotechnological processes. QS contributes to environmental adaptation via different models, by inducing the expression of genes that are required for the well-being of the organisms in a given milieu. To date, different kinds of autoinducers were detected in halophilic microorganisms (diketopiperazines, N-Acyl homoserine lactones, autoinducer-2), but the role of QS in this group of extremophiles needs to be elucidated yet. This chapter presents the recent advances in our understanding of bacterial intercommunication systems in halophilic bacteria.
Keywords: Quorum sensing; Halophiles; AHLs; Autoinducers; Quorum quenching; Extremophiles; PSEUDOMONAS-AERUGINOSA; GEN. NOV.; COMMUNICATION; LACTONES; MICROORGANISMS; IDENTIFICATION; DISRUPTION; INHIBITION; VIRULENCE; FISCHERI